Train duration and inter-train interval determine the direction and intensity of high-frequency rTMS after-effects - Jin, Jingna; Wang, Xin; Wang, He; Li, Ying; Liu, Zhipeng; Yin, Tao (Frontiers in Neuroscience, 2023)
It has been proved that repetitive transcranial magnetic stimulation (rTMS) triggers the modulation of homeostatic metaplasticity, which causes the effect of rTMS to disappear or even reverse, and a certain length of interval between rTMS trains might break the modulation of homeostatic metaplasticity. However, it remains unknown whether the effects of high-frequency rTMS can be modulated by homeostatic metaplasticity by lengthening the train duration and whether homeostatic metaplasticity can be broken by prolonging the inter-train interval. In this study, 15 subjects participated in two experiments including different rTMS protocols targeting the motor cortex. In the first experiment, high-frequency rTMS protocols with different train durations (2 s and 5 s) and an inter-train interval of 25 s were adopted. In the second experiment, high-frequency rTMS protocols with a train duration of 5 s and different inter-train intervals (50 s and 100 s) were adopted. A sham protocol was also included. Changes of motor evoked potential amplitude acquired from electromyography, power spectral density, and intra-region and inter-region functional connectivity acquired from electroencephalography in the resting state before and after each rTMS protocol were evaluated. High-frequency rTMS with 2 s train duration and 25 s inter-train interval increased cortex excitability and the power spectral density of bilateral central regions in the alpha frequency band and enhanced the functional connectivity between central regions and other brain regions. When the train duration was prolonged to 5 s, the after-effects of high-frequency rTMS disappeared. The after-effects of rTMS with 5 s train duration and 100 s inter-train interval were the same as those of rTMS with 2 s train duration and 25 s inter-train interval. Our results indicated that train duration and inter-train interval could influence the homeostatic metaplasticiy and determine the direction of intensity of rTMS after-effects. Clinicians and researchers should carefully consider the settings of train duration and inter-train interval when performing rTMS stimulation treatments and experiments.